2006
DOI: 10.1007/s11010-006-9374-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity of the p53 gene and deregulated expression of its mRNA and protein in human brain tumors

Abstract: Tumor-specific alterations at the p53 gene locus were analyzed in 40 human brain tumor samples. Gliomas were more prevalent in young males and meningiomas in old females. Structural changes at the intron 1 region of the p53 gene were analyzed in these tumors by Southern blotting. Among the 40 tumors, 33 were informative and 21 of these (63.6%) informative cases showed loss of heterozygosity (LOH). This is the first report showing LOH at the intron 1 region of p53 gene in human brain tumors. The level of p53 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In a study involving CNS embryonal tumors, 2/3 AT/RT cases showed staining for p53 (49). No definitive correlation exists between p53 expression by immunohistochemistry and TP53 mutations in either CNS or non-CNS malignancies (5054). There has been no systematic study of p53 immunohistochemistry and its relation to the mutational status in MRT.…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving CNS embryonal tumors, 2/3 AT/RT cases showed staining for p53 (49). No definitive correlation exists between p53 expression by immunohistochemistry and TP53 mutations in either CNS or non-CNS malignancies (5054). There has been no systematic study of p53 immunohistochemistry and its relation to the mutational status in MRT.…”
Section: Discussionmentioning
confidence: 99%
“…It is then distributed to other labs for research purpose only. The cells were propagated at 37 ∘ C with 5% CO 2 in a 95% humidified incubator as described previously [13,14]. The cells were fed with DMEM (Sigma-Aldrich, St. Louis, MO, USA) containing 10% fetal bovine serum (FBS) and propagated to approximately 70 to 80% confluency in 100 mm cell culture dishes in presence of penicillin (100 U/mL) and streptomycin (100 g/mL).…”
Section: Wi38 Cellsmentioning
confidence: 99%
“…The levels of protein bands were estimated by measuring the band intensities using Bio-Rad (Bio-Rad, Australia) quantity 1 software for all the samples individually, and these values were normalized to the corresponding control 48 kDa -tubulin bands from the same samples [27,28]. The levels of p53 protein in WI38 cell line were taken as 1.0 and the levels in untreated controls samples were calculated based on their intensities and reported as level of increase [13,14]. The protein levels in the treated samples were calculated for each tumor tissue based on the corresponding untreated control and reported as level of decrease in the treated samples [13,14].…”
Section: Specificity Of Control and P53mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of apoptosis may also contribute to drug resistance since chemotherapeutic agents mostly act by inducing apoptosis. The finding that brain tumors either deficient in the p53 tumor suppressor gene or over‐expressing the antiapoptotic protein Bcl‐2 escape apoptosis and are resistant to radiotherapy and chemotherapy (Rohini et al, 2006; Stegh et al, 2007) indicates that tumor‐specific genetic lesions confer a survival advantage to tumor cells. Malignant progression of gliomas involves accumulation of genetic alterations inactivating p53, p16, RB, and PTEN tumor suppressor genes and/or activating oncogenes including the epidermal growth factor receptor (EGFR), CDK4, CDK6, and MDM2 genes (Schiffer, 1998; Ushio et al, 2003).…”
mentioning
confidence: 99%